Synthesis, Drug Release, and Antibacterial Properties of Novel Dendritic CHX-SrCl2 and CHX-ZnCl2 Particles - Rui Sun; Jiaxin Zhang; Robert A. Whiley; Gleb B. Sukhorukov; Michael J. Cattell (MDPI AG, 2021)
This work demonstrated for the first time the synthesis of novel chlorhexidine particles containing strontium and zinc, to provide an effective, affordable, and safe intervention in the treatment of recurrent infections found in Medicine and Dentistry. The CHX-SrCl2 and CHX-ZnCl2 particles were synthesized by co-precipitation of chlorhexidine diacetate (CHXD) and zinc chloride or strontium chloride, where particle size was manipulated by controlling processing time and temperature. The CHX-ZnCl2 and CHX-SrCl2 particles were characterized using SEM, FTIR, and XRD. UV-Vis using artificial saliva (pH 4 and pH 7) was used to measure the drug release and ICP-OES ion release. The antibacterial properties were examined against P. gingivalis, A. actinomycetemcomitans, and F. nucleatum subsp. Polymorphum, and cytotoxicity was evaluated using mouse fibroblast L929 cells. The novel particles were as safe as commercial CHXD, with antibacterial activity against a range of oral pathogens. UV-Vis results run in artificial saliva (pH 4 and pH 7) indicated a higher release rate in acidic rather than neutral conditions. The CHX-ZnCl2 particles provided the functionality of a smart Zinc and CHX release, with respect to environmental pH, allowing responsive antibacterial applications in the field of medicine and dentistry.